Immediate Effects of Roller Massage for Posterior Neck Muscles on the Muscle Strength and Range of Motion for Cranio-Cervical Flexion in Subjects With Forward Head Posture - Seung-tak Kang; Jang-hun Jung; Oh-yun Kwon (Korean Research Society of Physical Therapy, 2021)
Background: Forward head posture (FHP) causes various posture imbalances associated with the head and neck. Myofascial release is an effective treatment method used for relaxing muscles and reducing muscle hyperactivity, but no studies have been conducted on suboccipital and neck muscles related to FHP. Objects: The purpose of this study was to investigate the immediate effect of roller massages on the cranio-cervical flexion (CCF) range of motion (ROM) and CCF strength applied to suboccipital and neck muscles in subject with forward head posture. Methods: Twenty-four FHP subjects (male: 13, female: 11) were recruited for this study. All subjects were recruited with a craniovertebral angle (CVA) of 53 degrees or less and a head tilt angle (HTA) of 20.66 degrees or higher. CCF strength was measured using Pressure biofeedback unit (PBU) in the supine posture and CCF ROM was measured using smartphone-based inclinometer. Roller massage (RM) was applied to suboccipital and neck muscles for 2 minutes and CCF ROM and strength were remeasured. Results: These results of this study showed that CCF ROM was a significant difference in CCF ROM before and after RM (p < 0.05). CCF strength also showed a significant difference before and after RM (p < 0.05). Conclusion: RM method might be recommended to increase the immediate ROM and strength of CCF in subjects with forward head posture.